Enhancement of magnetic properties of Ni0.5Zn0.5Fe2O4 nanoparticles prepared by the co-precipitation method. Issue 9 (July 2016) - Thakur, A.; Kumar, P.; Thakur, P.; Rana, K.; Chevalier, A.; Mattei, J.-L.; Queffélec, P.
Abstract: Nano crystalline Ni–Zn ferrites of composition Ni0.5 Zn0.5 Fe2 O4 have been prepared by a chemical co-precipitation method. The powdered samples were sintered at a temperature of 800 °C and 900 °C for three hours. X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared (FTIR) Spectroscopy were used to study their structural and morphological changes. The enhanced magnetic properties were investigated by using a Vibrating Sample Magnetometer (VSM). The saturation magnetization was found to increase from 73.88 to 89.50 emu/g as a function of sintering temperature making this material useful for high frequency applications. Electromagnetic studies showed sustained values of permittivity up to 1 GHz. These results have been explained on the basis of various models and theories.